Cardiac surgery in patients with previous hepatic or renal transplantation: a pair-matched study - Farag, Mina; Nikolić, Marina; Arif, Rawa; Schmack, Bastian; Ruhparwar, Arjang; Karck, Matthias; Weymann, Alexander (The annals of thoracic surgery, 2017)
The objective of this study was to compare outcomes of patients with previous solid organ transplant with those of a pair-matched population. Data from our prospectively maintained cardiac surgery registry were obtained and identified 70 transplant recipients (21 hepatic, 49 renal) who were operated on at our department of cardiac surgery between 2000 and 2013; they formed the transplant group. Those patients were pair-matched regarding age, sex, and cardinal cardiac risk factors to form the pair-matched group.